Increasing Higher Education Promotion Through a Coverage Focus Strategy for Mapping Characteristics of New Students - Daryono, Daryono (STAI Miftahul Ula Nganjuk, 2022)
Nowadays, the promotion of higher education in Indonesia in attracting prospective students is quite intense. In the digital era, the role of digital media occupies the highest role in providing access to information and communication so that it becomes the most effective service used by universities. The coverage focus strategy is an option to incorporate digital media to find out the characteristics of new students. This research is a qualitative research using a descriptive approach. This study aims to determine the promotion strategy using the coverage focus technique and to determine the characteristics of prospective new students in tertiary institutions. The subjects in this study consisted of the college promotion team and prospective new students at Universitas PGRI WIRANEGARA. Data were collected through interviews and questionnaires, then analyzed using data triangulation techniques. The results of the study show that the promotion strategies carried out by Universitas PGRI WIRANEGARA are Advertising, Personal Selling, Publicity, and Word of Mouth. The characteristics of prospective new students at Universitas PGRI WIRANEGARA after not being accepted by the SBMPTN are showing an interest in further studies, learning motivation, intellectual level, economic level and parental support